2023
DOI: 10.1002/alz.12908
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer‐measured physical activity and sitting with incident mild cognitive impairment or probable dementia among older women

Abstract: Introduction: Physical activity (PA) is prospectively inversely associated with dementia risk, but few studies examined accelerometer measures of PA and sitting with rigorously-adjudicated mild cognitive impairment (MCI) and dementia risk. Methods:We examined the associations of accelerometer measures (PA and sitting) with incident MCI/probable dementia in the Women's Health Initiative (n = 1277; mean age = 82 ± 6 years)Results: Over a median follow-up of 4.2 years, 267 MCI/probable dementia cases were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 75 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…Previous work found that self-reported leisure-time sedentary behaviors were associated with risk of developing all-cause dementia, and the direction of the risk depended on the activity done while sedentary (ie, cognitively passive TV watching vs cognitively active computer use) . However, a recent study using accelerometer-derived sitting time did not find an association between sedentary behaviors and incident dementia in a sample of older women (n = 1277) …”
Section: Introductionmentioning
confidence: 92%
“…Previous work found that self-reported leisure-time sedentary behaviors were associated with risk of developing all-cause dementia, and the direction of the risk depended on the activity done while sedentary (ie, cognitively passive TV watching vs cognitively active computer use) . However, a recent study using accelerometer-derived sitting time did not find an association between sedentary behaviors and incident dementia in a sample of older women (n = 1277) …”
Section: Introductionmentioning
confidence: 92%
“…Although some accelerometry studies have identified sedentary activity as an outcome associated with prevalent dementia (Hartman et al, 2018) or incident dementia (Raichlen et al, 2023), other studies have had less convincing results. For example, in a study of self-reported leisure time (Raichlen et al, 2022), investigators found that spending more sedentary time watching television was associated with an increased risk of incident dementia, but spending more sedentary time on the computer was associated with a decreased risk of incident dementia, and in an accelerometry study, other investigators found no association between sedentary behaviors and incident dementia in a sample of older women (Nguyen et al, 2023). These inconsistent findings suggest that additional studies are needed to better understand how sedentary behaviors are related to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…A previous SAGE cohort study by Huang et al investigated the contemporaneous association of five modifiable lifestyle factors with age-related cognitive decline and found that higher levels of physical activity were positively associated with all cognitive domains ( 38 ). A recent study among women aged 65 and over showed that an extra 31 min of moderate to strenuous physical activity every day reduced the prevalence of mild cognitive impairment or dementia by 21% ( 39 ). In addition, a previous study by our team showed that physical performance (grip strength, TUGT, and 4-m walking speed) correlated with MCI ( 13 ).…”
Section: Discussionmentioning
confidence: 99%